Rapid detection of medium chain acyl-CoA dehydrogenase gene mutations by non-radioactive, single strand conformation polymorphism minigels. Issue 7 (July 1994) - Iolascon, A; Parrella, T; Perrotta, S; Guardamagna, O; Coates, P M; Sartore, M; Surrey, S; Fortina, P
Abstract : Medium chain acyl-CoA dehydrogenase (MCAD) deficiency is a common inherited metabolic disorder affecting fatty acid beta oxidation. Identification of carriers is important since the disease can be fatal and is readily treatable once diagnosed. Twelve molecular defects have been identified in the MCAD gene; however, a single highly prevalent mutation, A985G, accounts for > 90% of mutant alleles in the white population. In order to facilitate the molecular diagnosis of MCAD deficiency, oligonucleotide primers were designed to amplify the exon regions encompassing the 12 mutations enzymatically, and PCR products were then screened with a single strand conformation polymorphism (SSCP) based method. Minigels were used allowing much faster run times, and silver staining was used after gel electrophoresis to eliminate the need for radioisotopic labelling strategies. Our non-radioactive, minigel SSCP approach showed that normals can be readily distinguished from heterozygotes and homozygotes for all three of the 12 known MCAD mutations which were detected in our sampling of 48 persons. In addition, each band pattern is characteristic for a specific mutation, including those mapping in the same PCR product like A985G and T1124C. When necessary, the molecular defect was confirmed using either restriction enzyme digestion of PCR products or by direct DNA sequence analysis or both. This rapid, non-radioactive approach can become routine for molecular diagnosis of MCAD deficiency and other genetic disorders.